Fecal microbiota transplantation augmented by a sulfide‐reducing diet for refractory ulcerative colitis: A case report with functional metagenomic analysis. Issue 9 (29th July 2021) - Bryant, Robert V; Day, Alice S; McGrath, Ken C; Telfer, Karmen; Yao, Chu K; Costello, Samuel P
Abstract: Fecal microbiota transplantation (FMT) is effective for induction of remission in ulcerative colitis (UC). Diet has potential to augment the efficacy and durability of FMT by encouraging engraftment of transplanted microorganisms. A trial of FMT combined with a defined diet was undertaken as salvage therapy for a 71‐year‐old woman with active steroid‐refractory extensive UC. A multidimensional sulfide‐reducing diet (4‐SURE diet) was commenced followed by single‐donor FMT administered by colonoscopy and then enemas over 7 days. Dietary adherence, clinical evaluation, and stool samples for metagenomic profiling were undertaken at weeks 0, 4, 8, and 24. Colonoscopy was performed 8 weeks post‐FMT. Shotgun metagenomic profiling of the donor fecal suspension was also performed. A rapid clinical response to FMT and 4‐SURE diet was observed with normalization of stool frequency (≤2 motions/day) and resolution of rectal bleeding within 2 weeks. Dietary adherence was excellent. Colonoscopy at week 8 revealed no evidence of active colitis (Mayo endoscopic sub‐score 0) with histology showing no evidence of acute or chronic lamina propria inflammatory cell infiltrate. Sustained clinical and endoscopic remission out to 24 weeks was observed. Metagenomic sequencing confirmed sustained engraftment of beneficial donor microbiota with increased alpha‐diversity and capacity for short‐chain fatty acid production, including Faecalibacterium prauznitzii and Eubacterium hallii . This case report supports the rationale of prescribed diet therapy to support engraftment of donor microbiota following FMT for UC. Further large trials with a diet‐arm control group are needed to evaluate FMT augmented by a defined diet in UC. Abstract : Durable efficacy and sustained remission to 24 weeks associated with microbial engraftment of induction fecal microbiota transplantation augmented by diet are observed in a patient with refractory ulcerative colitis (UC). Metagenomic sequencing confirmed sustained engraftment of beneficial donor microbiota with increased alpha‐diversity and capacity for short‐chain fatty acid production, including Faecalibacterium prauznitzii and Eubacterium hallii . Mechanistic insights provided by functional microbiome analysis illustrate a synergistic combined approach to microbial manipulation in UC.